1998
DOI: 10.1126/science.281.5382.1500
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Synthesis of Zintl Compounds with a Single-Source Molecular Precursor

Abstract: Thermolysis of the heterobimetallic phosphinidene complex [Sb(PCy)3]2- Li6.6HNMe2 (Cy = C6H11) at 303 to 313 kelvin gives Zintl compounds containing (Sb7)3- anions. The complex thus constitutes a stable molecular single-source precursor to Zintl compounds and provides a potential low-temperature route to photoactive alkali metal antimonates. The new chemical reaction involved, which is driven thermodynamically by the formation of P-P bonds, has implications in the low-temperature synthesis of other technologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 25 publications
4
41
0
Order By: Relevance
“…Wright et al. reported on the synthesis of the Zintl compound [Sb 7 Li 3 ⋅6 HNMe 2 ] by controlled thermolysis reaction of {[Sb(PCy) 3 ] 2 Li 6 ⋅6 HNMe 2 } in toluene at low temperature (40 °C), whereas in recent years Kloo, Burford, and Weigand et al. established reductive catenation reactions for the synthesis of Group 15 polycations…”
Section: Introductionmentioning
confidence: 99%
“…Wright et al. reported on the synthesis of the Zintl compound [Sb 7 Li 3 ⋅6 HNMe 2 ] by controlled thermolysis reaction of {[Sb(PCy) 3 ] 2 Li 6 ⋅6 HNMe 2 } in toluene at low temperature (40 °C), whereas in recent years Kloo, Burford, and Weigand et al. established reductive catenation reactions for the synthesis of Group 15 polycations…”
Section: Introductionmentioning
confidence: 99%
“…This intrigued us, as previous studies have shown that heterometallic group 15/alkali metal phosphanediides compounds (e.g., [12] ) decompose into Zintl ions and metallic alloys. [13] As illustrated in Scheme 6, this process occurs through heterocyclic anions of the type [(RP) m E] À and is driven by the thermodynamics of P À P single-bond formation. We wondered whether similar chemistry was occurring in the thermal decomposition of 1 a-c.…”
Section: Resultsmentioning
confidence: 99%
“…Solid 1 a , 1 b and 1 c are relatively stable at room temperature under dry, O 2 ‐free N 2 for days, decomposing only slowly at this temperature to give metallic‐looking residues. This intrigued us, as previous studies have shown that heterometallic group 15/alkali metal phosphanediides compounds (e.g., [{Sb(PCy) 3 } 2 (Li ⋅ NHMe 2 ) 6 ]12) decompose into Zintl ions and metallic alloys 13. As illustrated in Scheme , this process occurs through heterocyclic anions of the type [(RP) m E] − and is driven by the thermodynamics of PP single‐bond formation.…”
Section: Resultsmentioning
confidence: 99%
“…Lithiation of 1,2‐(PH 2 ) 2 C 6 H 4 (1 equiv) with n BuLi (2 equiv) in tmeda (tmeda=Me 2 NCH 2 CH 2 NMe 2 ) followed by reaction with Sb(NMe 2 ) 3 (0.67 equiv) gives [Li(tmeda) 2 ] + [1,2‐C 6 H 4 P 2 Sb] − ( 1 ) after crystallization from THF/tmeda. However, black crystals of [{1,2‐C 6 H 4 P 2 Sb} 2 {Li(tmeda)} 4 ] ( 2 )6 are obtained if this reaction is undertaken in toluene and the product crystallized from toluene/tmeda. Compound 2 presumably arises from one‐electron reduction of the 6π‐aromatic anion of 1 (Scheme ).…”
Section: Methodsmentioning
confidence: 99%